REVEAL THE ROLE OF GARLIC SILVER NANOPARTICLES AND GARLIC ZINC NANOPARTICLES ON CANDIDA ALBICANA ISOLATED FROM WOMEN WITH VULVOVAGINAL CANDIDIASIS - Abid, Hawazin Ahmed (Journal of Medical Genetics and Clinical Biology, 2024)
The current investigation aimed to reveal the role of garlic silver nanoparticles and garlic zinc nanoparticles on Candida albicana isolated from women with Vulvovaginal Candidiasis. 120 clinical samples were collected during the period from February to May 2024 from married female patients, collected from Salah al-Din General Hospital. Samples were collected for women with vaginal candidiasis whose ages ranged from (20-50 years). The initial diagnosis and examination for follow-up examinations were conducted with the assistance of a female gynecologist. The results of the microscopic and morphological examination of the total number of samples (120) showed that there were 69(57.5%) positive samples, while the number of negative samples was 51(42.5%). The molecular assay was positive for all DNA samples from the patients with Vulvovaginal Candidiasis, with Cq values ranging (24.402- 29.437) for ALS1 gene, (14.748-29.562) for HWP1 and (23.699-28.23) for ACT1. Results showed 9(90.0%), 10(100.0%) and 7(70.0%) of C. albicans isolates had ALS1, HWP1 and ACT1 gene respectively, which is one of the virulence factors in yeast C. albicanes. On the other hand, the results of the current study demonstrate the effectiveness of both AgNPs and ZnO NPs against Candida albicans. A concentration of 250 and 500 ppm was used for both AgNPs and ZnO NPs. It was found that the average diameter of the inhibition zone for 10 isolates tested was (8.04±3.47) and (21.25±3.18) for AgNPs. prepared with garlic, and the average diameter of the inhibition zone for 10 isolates tested was (8.99±2.24) and (19.57±2.54) for ZnO NPs prepared with garlic. It is concluded from the current study that both AgNPs and ZnO NPs prepared with garlic extract have inhibitory activity against Candida albicans.